2018
DOI: 10.3390/cancers10120493
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in the Metastatic Process of High-Risk HPV-Induced Cancers

Abstract: High-risk human papillomavirus (HPV)-driven cancers represent a major health concern worldwide. Despite the constant effort to develop and promote vaccination against HPVs, there is still a high percentage of non-vaccinated population. Furthermore, secondary prevention programs are not ubiquitous worldwide and not widely followed. Metastatic disease is the cause of the great majority of cancer-associated deaths, making it essential to determine its underlying mechanisms and to identify actionable anti-metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 121 publications
0
22
0
Order By: Relevance
“…Nuclei were visualised using DAPI (blue). Images were acquired using identical PLOS PATHOGENS miR-18a is upregulated in HPV+ cervical cancer and directly targets STK4 mRNA Both HPV E6 and E7 can modulate the microRNA (miRNA) network as a mechanism to control host gene expression [35][36][37]. The oncomiR miR-18a, a member of the oncogenic miR-17-92 cluster, is highly expressed in cervical cancer and has been shown to contribute to the proliferative and invasive phenotype, through ill-defined mechanisms [38,39].…”
Section: Fig 3 Inhibition Of Stk4/3 Kinase Activity Prevents the Blomentioning
confidence: 99%
“…Nuclei were visualised using DAPI (blue). Images were acquired using identical PLOS PATHOGENS miR-18a is upregulated in HPV+ cervical cancer and directly targets STK4 mRNA Both HPV E6 and E7 can modulate the microRNA (miRNA) network as a mechanism to control host gene expression [35][36][37]. The oncomiR miR-18a, a member of the oncogenic miR-17-92 cluster, is highly expressed in cervical cancer and has been shown to contribute to the proliferative and invasive phenotype, through ill-defined mechanisms [38,39].…”
Section: Fig 3 Inhibition Of Stk4/3 Kinase Activity Prevents the Blomentioning
confidence: 99%
“…many miRNAs are related to the occurrence, development and spread of cancer. 22,23 miRNA, as a key regulator, is involved in almost all cellular processes in mammals and other multicellular organisms, regardless of its carcinogenic or anticancer roles. 20 Current studies 24 have shown that various types of malignant tumors are associated with miRNA disorders, and about 50% of the known human miRNA are susceptible to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of E6/E7 promotes genetic instability and chromosomal rearrangements that enhance the risk of integration [46]. Similarly, deregulation of viral gene expression deregulates the cell cycle via p53 and Rb degradation, deregulation of oncogenes and miRNAs expression [[47], [48], [49], [50]]. Without a doubt, further investigation is required to determine the detailed mechanisms of HPV-induced cervical cancer.…”
Section: Systems Biology Approaches In Cervical Cancermentioning
confidence: 99%